PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN PEMAHAMAN KONSEP PANCA INDRA PADA SISWA KELAS III SD - Rossa Aulia Putri Barus; Kms. Muhammad Amin Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Understanding the concept of the five senses in elementary school students is still often a challenge, mainly because the learning process tends to focus on memorization and one-way explanations. This condition makes it difficult for students to connect the material with real experiences. This study aims to improve the understanding of the concept of the five senses in third-grade students through the application of a guided inquiry model. This classroom action research used a quantitative approach with 26 third-grade students of SDN 105337 Pantai Labu Pekan as subjects. The learning action was carried out in three meetings involving experimental activities, group discussions, and poster making. Data were obtained through diagnostic, formative, and summative assessments, including multiple-choice student worksheets (LKPD), process observations, and creative product assessments. The results showed that the guided inquiry model was able to increase student engagement in the learning process and strengthen understanding of the five senses concept. Most students achieved the "Good" to "Very Good" category, while only a few were in the "Sufficient" and "Poor" categories. The poster products produced by students also demonstrated their ability to connect the material to the context of everyday life and local wisdom values. Overall, the application of guided inquiry proved effective in developing students' cognitive, affective, and psychomotor aspects while creating more interactive, meaningful, and contextual learning. These findings confirm that the guided inquiry approach can be a relevant alternative learning strategy to improve the quality of science learning in elementary schools.